Structural breaks in Iron-Ore prices: The impact of the 1973 oil crisis - Nikolay Angelov (Uppsala University, Department of Economics, 2006)
This paper investigates the time-series properties of the price of iron ore. The focus is on testing a unit-root null hypothesis against a trend-stationary alternative, with a structural break allowed under both hypotheses. We consider unit-root tests with or without structural breaks, applied on historical prices of five different qualities of Swedish and Brazilian iron ore. New and more accurate critical values for the exogenous-break tests are calculated, and several of the asymptotic tests are accompanied by their bootstrap counterparts due to the limited sample sizes. Using unit-root tests allowing for an exogenous structural break in 1973, the null hypothesis of a unit root is rejected for three of the five series. The sign and nature of the estimated breaks correspond to the state of the iron and steel industry during the first half of the 1970s. The bootstrap tests give results close to those from the asymptotic ones.
urn:nbn:se:uu:diva-83078
Keywords: C15; C22; Q30; 330; iron-ore prices; structural break; unit-root test; bootstrap; Eisenerz; Preis; Ölpreis; Strukturbruch; Unit Root Test; Bootstrap-Verfahren